2018
DOI: 10.1002/ldr.3104
|View full text |Cite
|
Sign up to set email alerts
|

How does land management contribute to the resilience of Mediterranean forests and rangelands? A participatory assessment

Abstract: In Mediterranean forests and rangelands, the supply of important ecosystem services can decrease or cease as a consequence of disturbances and climatic oscillations. Land managers can sometimes prevent or mitigate the negative effects of disturbances through appropriate land management choices. In this study, we assess the contribution of land management practices (LMPs) to the resilience of eight Mediterranean forests and rangelands to multiple disturbances. The study uses a transdisciplinary approach, involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
(136 reference statements)
0
7
0
Order By: Relevance
“…Existing land management practices were subsequently assessed using the standard World Overview of Conservation Approaches and Technologies (WOCAT) technology questionnaire (Wocat, 2008) with stakeholder involvement. Findings from this assessment formed the basis of an in-depth study on sustainability and resilience of land management practices vis-à-vis ecosystem thresholds and disturbances (Jucker Riva et al, , 2018.…”
Section: Participatory Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Existing land management practices were subsequently assessed using the standard World Overview of Conservation Approaches and Technologies (WOCAT) technology questionnaire (Wocat, 2008) with stakeholder involvement. Findings from this assessment formed the basis of an in-depth study on sustainability and resilience of land management practices vis-à-vis ecosystem thresholds and disturbances (Jucker Riva et al, , 2018.…”
Section: Participatory Assessmentmentioning
confidence: 99%
“…Understanding how we can better manage ecosystems vulnerable to catastrophic shifts requires an appreciation of how land management practices contribute to or reduce resilience to stresses, mitigate land degradation or rehabilitate degraded areas with long lasting effects (Jucker Riva et al, , 2018. Research participants and local stakeholders identified, assessed and evaluated relevant management practices in each study site (Figure 7).…”
Section: How Can We Better Manage Vulnerable Ecosystems?mentioning
confidence: 99%
See 3 more Smart Citations